Correlating The Diagnostic Accuracy of Radiological Imaging and Histological Findings in the Diagnosis of Non-Alcoholic Fatty LiverDisease(NAFLD) Among Patients in a Tertiary Hospital (Western Journal of Medical and Biomedical Sciences, 2024)
This study aimed to evaluate the diagnostic accuracy of ultrasound in diagnosing non-alcoholic fatty liver diseases (NAFLD) compared to biopsy. In this study, participants were recruited patients with fatty liver who underwent liver biopsy and baseline ultrasound at the University of Calabar Teaching Hospital between January 2023 and December 2023. Ultrasonographic findings were correlated with the histological findings of liver biopsy which was considered as the gold standard for the diagnosis of NAFLD. Atotal of 109 subjects were recruited and participated in this study. This comprised 62(56.9%) females and 47(43.1%) males with the highest age bracket presenting at 56-65 years. The mean age of the study participants was 55.5±12.8years (age range was 18-70 years). The female-to-male ratio was 1:1.4. The ultrasonographic findings were correlated with histological data (considered as the gold standard). The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were evaluated. The ultrasonography had a sensitivity of 90.4% (95% confidence interval:83.6-93.6), and specificity of 72.5% (95% confidence interval  68.7-79.8). The PPV and NPV were 74.7% and 65.6% respectively. The area under the curve was 84.5%. The positive likelihood ratio was 1.5(95CI :1.21-1.90), and negative likelihood ratio was 0.30(0.17-0.54).Ultrasound findings are highly significant and useful in detecting advanced steatosis in patients with fatty liver. In the future, as technology advances, it is hoped that the need for liver biopsy may not be necessary as hi-tech radiological involvement may help  patients with fatty liver without participation in any invasive procedure.
Keywords: Biopsy; Calabar; Fatty liver; Radiological; Steatosis; Ultrasound